Conflict within species determines the value of a mutualism between species. Issue 2 (6th March 2019) - Sun, Syuan‐Jyun; Horrocks, Nicholas P. C.; Kilner, Rebecca M.
Abstract: Mutually beneficial interactions between species play a key role in maintaining biodiversity and ecosystem function. Nevertheless, such mutualisms can erode into antagonistic interactions. One explanation is that the fitness costs and benefits of interacting with a partner species vary among individuals. However, it is unclear why such variation exists. Here, we demonstrate that social behavior within species plays an important, though hitherto overlooked, role in determining the relative fitness to be gained from interacting with a second species. By combining laboratory experiments with field observations, we report that conflict within burying beetles Nicrophorus vespilloides influences the fitness that can be gained from interacting with the mite Poecilochirus carabi . Beetles transport these mites to carrion, upon which both species breed. We show that mites help beetles win intraspecific contests for this scarce resource: mites raise beetle body temperature, which enhances beetle competitive prowess. However, mites confer this benefit only upon smaller beetles, which are otherwise condemned by their size to lose contests for carrion. Larger beetles need no assistance to win a carcass and then lose reproductive success when breeding alongside mites. Thus, the extent of mutualism is dependent on an individual's inability to compete successfully and singlehandedly with conspecifics. Mutualisms degrade into antagonism when interactions with a partner species start to yield a net fitness loss, rather than a net fitness gain. This study suggests that interactions with conspecifics determine where this tipping point lies.